Comment on 3PL IRT Adjustment for Guessing. (January 2013) - Chiu, Ting-Wei; Camilli, Gregory
Guessing behavior is an issue discussed widely with regard to multiple choice tests. Its primary effect is on number-correct scores for examinees at lower levels of proficiency. This is a systematic error or bias, which increases observed test scores. Guessing also can inflate random error variance. Correction or adjustment for guessing formulas has been applied to address some of these issues. The purpose of this research comment is to draw attention to the adjustment for guessing implicit in the three-parameter logistic item response theory model. Potential equity issues also arise with respect to this adjustment.